2019
DOI: 10.1371/journal.pone.0213310
|View full text |Cite
|
Sign up to set email alerts
|

The faster, the better? Relationships between run-up speed, the degree of difficulty (D-score), height and length of flight on vault in artistic gymnastics

Abstract: On vault in artistic gymnastics, a high run-up speed is thought to be important when performing difficult vaults. To test this assumption in a large cohort of elite athletes, we calculated the correlations between the run-up speed, scores, height and length of flight for handspring-, Tsukahara- and Yurchenko-style vaults and compared the performances of male and female elite and junior athletes (n = 407) during the 2016 European Championships. In females, run-up speed correlated significantly with the difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…Correlation coefficients were compared according to Eid, Gollwitzer [19]. The model was created based on findings of previous studies that found 1) that D-score on vault is closely related with run-up velocity [7], 2) that maximal sprint speed represents the exploitable potential during run-up, 3) that (any) sprint speed is determined as the product of step length and step frequency [13] and 4) that lower body power is important in order to perform fast sprints over short distances [20]. Age-related differences of D-score, run-up speed, run-up kinematics and lower body power were calculated only for Ha/Ts vaults, due to the small number of athletes that performed Yu vaults.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Correlation coefficients were compared according to Eid, Gollwitzer [19]. The model was created based on findings of previous studies that found 1) that D-score on vault is closely related with run-up velocity [7], 2) that maximal sprint speed represents the exploitable potential during run-up, 3) that (any) sprint speed is determined as the product of step length and step frequency [13] and 4) that lower body power is important in order to perform fast sprints over short distances [20]. Age-related differences of D-score, run-up speed, run-up kinematics and lower body power were calculated only for Ha/Ts vaults, due to the small number of athletes that performed Yu vaults.…”
Section: Methodsmentioning
confidence: 99%
“…In this context it must be mentioned that the different vault styles Handspring, Tsukahara and Yurchenko (Fig 1) require different levels of run-up speed. Handspring and Tsukahara (Ha/Ts) style vaults are generally performed with higher run-up speeds than Yurchenko (Yu) style vaults [7]. Contrary to Ha/Ts vaults (forward take-off from vaulting board), for Yu vaults, the gymnasts perform a round-off in front of the vaulting board and backwards handspring on the vaulting table.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations